How much wrapping do babies need at night?. Issue 2 (August 1993) - Wigfield, R E; Fleming, P J; Azaz, Y E; Howell, T E; Jacobs, D E; Nadin, P S; McCabe, R; Stewart, A J
Abstract : In a longitudinal, population based study, overnight temperature recordings were made in the bedrooms of 152 babies aged 3-18 weeks and the insulation provided by their bedclothing was assessed. Outdoor temperatures for the study nights were also available. Parents applied more insulation on colder nights with lower bedroom temperatures than on warmer nights (mean 8.5 tog at 15 degrees C minimum bedroom temperature falling to 4.0 tog at 25 degrees C). For a particular temperature they also applied 2 tog more insulation in winter than in summer. The amounts of bedclothing used in the home were compared with insulation levels predicted to achieve thermo-neutrality over a similar range of environmental temperature from heat balance studies in young infants. They corresponded closely. The average amount of bedclothing chosen for babies in Avon allows them to remain in thermoneutral conditions throughout the night. These values are proposed as broad guidelines for the thermal care of young babies at night.